Geometrical pinning of magnetic vortices induced by a deficit angle on a surface: anisotropic spins on a conic space background - Moura-Melo, W. A.; Pereira, A. R.; Mól, L. A. S.; Pires, A. S. T. (Physics Letters A, 2007)
We study magnetic vortex-like excitations lying on a conic space background. Two types of them are obtained. Their energies appear to be linearly dependent on the conical aperture parameter, besides of being logarithmically divergent with the sample size. In addition, we realize a geometrical-like pinning of the vortex, say, it is energetically favorable for it to nucleate around the conical apex. We also study the problem of two vortices on the cone and obtain an interesting effect on such a geometry: excitations of the same charge, then repealing each other, may nucleate around the apex for suitable cone apertures. We also pay attention to the problem of the vortex pair and how its dissociation temperature depends upon conical geometry.
Keywords: Magnetic vortices; Anisotropic